FINANCIAL STABILITY OF THE INSURANCE COMPANY AND KEY CONDITIONS FOR ITS PROVIDING - Olha Boronina (Соціальна економіка)
In the article, we considered the evaluation of the financial reliability of insurance organizations. The insurer’s financial reliability usually means the insurer’s ability to fulfill insurance obligations under insurance and reinsurance contracts in the event of adverse factors. We investigated that the financial stability of an insurance organization is a complex indicator that depends on both internal and external factors. We studied the main classifications of factors that affect the level of financial stability of an insurance organization: according to the possibility of management and depending on direct and indirect influence. We have analyzed the main approaches to assessing the financial reliability of an insurance organization. We proposed approaches using single indicators (liquidity indicator, solvency indicators, reinsurance indicators, etc.), systems of relative indicators and integral indicators. We identified the advantages and disadvantages of such approaches, analyzed the advantages and disadvantages of early warning tests for assessing the financial reliability of an insurance organization, and showed that the advantage of using integral indicators is the ease of application and the possibility of taking into account various factors. However, when using integral indicators, certain difficulties arise, which are associated with the fact that, as a rule, partial indicators that have different dimensions are combined into an integral indicator, therefore, for their combination or convolution, each of the partial indicators should be transformed into a dimensionless quantity using the appropriate scale. In order to build an integral indicator for assessing the financial reliability of an insurance organization, it is recommended to use the Harrington method and take into account the factors that characterize the activity of an insurance organization: internal: (level of payments; provision of insurance reserves; reinsurer participation; solvency ratio; current liquidity ratio; reinsurance ratio) and external factors that take into account the general economic situation in the country and the efficiency of the functioning of the state’s economy (inflation rate; GDP growth rates).